Evaluation of accidental exposures in laboratories\' personnel in Teaching Hospitals of Tehran University of Medical Sciences(TUMS) during 2004 to 2005 - M Rabieyan; R Safdari; M Rahimkhani; R Sharifian; A Molaeezadeh (Tehran University of Medical Sciences, 2008)
Background and Aim: The risk of infectious diseases in laboratory's personnel is high and several factors can increase these risk. Some of these factors are general, such as burning (with stray acid and base) and electric shock hazards. Which are not exclusive for laboratories. In other hand some several risk factors such as burning liquids are exclusive for laboratories. And there is limited information available about them. Materials and Methods: This cross-sectional study was designed to evaluate accidental exposures of all laboratories personnel of Teaching Hospitals of Tehran University of Medical Sciences during 2004- 2005. We selected 416 laboratories personnel's in 15 different teaching hospitably TUMS for our study. The data were collected using a questionnaire and SPSS software was applied for data analysis. Results:There was no significant association between accidental exposures with gender (p=0.51), educational level (p=0.11) and age (0.09) of laboratories personnel. But, accidental exposures were lower among those who had job experience between 5 to 10 years (p<0.05) compare to less than 5 years or more than 10 years job experience. Conclusions:Although age, gender and educational level of laboratories personnel did not influence their exposure to laboratory's accidents, little or extensive job experience may increase accidental exposures among them.